2014
DOI: 10.1371/journal.pone.0101680
|View full text |Cite
|
Sign up to set email alerts
|

Social Category Formation Is Induced by Cues of Sharing Knowledge in Young Children

Abstract: Previous research has shown that human infants and young children are sensitive to the boundaries of certain social groups, which supports the idea that the capacity to represent social categories constitutes a fundamental characteristic of the human cognitive system. However, the function this capacity serves is still debated. We propose that during social categorization the human mind aims at mapping out social groups defined by a certain set of shared knowledge. An eye-tracking paradigm was designed to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Young children, therefore, do not discriminate based on any arbitrary cue (e.g., colored arm band; Plötner, Over, Carpenter, & Tomasello, 2015), while the language the potential partner speaks is a fundamental group-relevant characteristic to guide their preferences (Buttelmann et al, 2013;Howard, Henderson, Carrazza, & Woodward, 2015). Moreover, it seems that the conventionality of tool-using behavior is also a relevant indicator of in-group-out-group membership: Even 2-year-olds tend to associate foreign and native languages differentially with people based on the conventionality of the adult's toolusing behavior (Oláh, Elekes, Bródy, & Király, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Young children, therefore, do not discriminate based on any arbitrary cue (e.g., colored arm band; Plötner, Over, Carpenter, & Tomasello, 2015), while the language the potential partner speaks is a fundamental group-relevant characteristic to guide their preferences (Buttelmann et al, 2013;Howard, Henderson, Carrazza, & Woodward, 2015). Moreover, it seems that the conventionality of tool-using behavior is also a relevant indicator of in-group-out-group membership: Even 2-year-olds tend to associate foreign and native languages differentially with people based on the conventionality of the adult's toolusing behavior (Oláh, Elekes, Bródy, & Király, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Allocating more attention to someone speaking the same language (3,15) would be a sensible learning strategy, given that language can indicate a common culture and a native speaker is therefore more likely to convey relevant information than a nonnative speaker. Indeed, it has been shown that 2-y-olds expect foreign language use to associate with other cultural knowledge, such as unconventional tool use, supporting the hypothesis that social categories, such as linguistic groups, may be formed based on, and with the function of, defining barriers of culturally shared knowledge (16). Infants' preference for the conventions (6), food preferences (4), and musical tastes (5) conveyed by a native language speaker is consistent with this hypothesis because it is exactly these kinds of arbitrary, culturally dependent phenomena that a same-group member would be best placed to transmit.…”
mentioning
confidence: 83%
“…Infants and young children are more likely to adopt behaviors and preferences, if they are endorsed by members of their linguistic ingroup (Buttelmann, Zmyj, Daum, & Carpenter, 2013;Kinzler, Corriveau, & Harris, 2011;Kinzler, Dupoux, & Spelke, 2007;Shutts, Kinzler, McKee, & Spelke, 2009;Soley & Sebasti an-Gall es, 2015). Starting around the age of 2 years, children associate conventional actions with native speakers (Liberman, Howard, Vasquez, & Woodward, 2018;Ol ah, Elekes, Br ody, & Kir aly, 2014), they expect normative behaviors to apply to members of the same group (Kalish, 2012;Weatherhead, White, & Friedman, 2016), and they enforce norms selectively to ingroup members (Schmidt, Rakoczy, & Tomasello, 2012). Previous research also suggests that 3-to 6-year-old children consider social norms (e.g., the rules of a game) to be specific to social groups, but moral norms (e.g., not to steal from someone) to be applicable to everyone (Liberman, Howard et al, 2018).…”
Section: Introductionmentioning
confidence: 99%